INTEGRATION OF EVIDENCE-BASED MEDICINE INTO CLINICAL MICROBIOLOGY PRACTICE - Карбованець, Олена (SWorldJournal, 2025)
Objective: To summarize the principles of evidence-based medicine (EBM) in clinical microbiology and demonstrate how their application enhances the clinical relevance of microbiological studies, the quality of diagnostics, and decision-making in antimicro